Budaya Sekolah Islami (BUSI): Studi Kasus di SMA Islam Sultan Agung 1 Semarang - Mustopa, Mustopa (FITK UIN Walisongo, 2017)
The value crisis has affected the Indonesian people in all areas of life including education. These conditions lead to the importance of intensive value education in schools. This paper aims to find out the concept of Islamic School Culture (Busi) and its implementation pattern in SMA Islam Sultan Agung 1 Semarang. The type of this research is descriptive qualitative. The result of the research shows that Busi in Sultan Agung 1 Semarang Islamic High School includes iqra 'culture, congregational prayer culture, thaharah culture, social interaction culture, and exemplary culture. The implementation pattern has been using top down with three step: socialization, habituation and monitoring. This pattern has succeeded in applying these Islamic values to unite in other school cultural activities in accordance with the vision, mission and objectives of the institution.Â AbstrakKrisis nilai telah menimpa bangsa Indonesia pada semua bidang kehidupanÂ termasuk dunia pendidikan. Kondisi seperti ini menyebabkan pentingnya pendidikan nilai secara intensif di sekolah-sekolah. Tulisan ini bertujuan untuk mengetahui konsep Budaya Sekolah Islami (Busi) dan pola pelaksanaannya di SMA Islam Sultan Agung 1 Semarang. Jenis penelitian ini adalah deskriptif kualitatif. Hasil penelitian menunjukkan bahwa Busi di SMA Islam Sultan Agung 1 Semarang meliputi budaya iqra, budaya shalat berjamaah, budaya thaharah, budaya pergaulan islami, dan budaya keteladanan. Â Pola Pelaksanaan Busi dilaksanakan secara top down dengan tahapan sosialisasi, pembiasaan dan monitoring. Pola ini telah berhasil menerapkan nilai-nilai Islam tersebut menyatu dalam aktifitas budaya sekolah yang lain sesuai dengan visi, misi dan tujuan lembaga